The jewish situation in the protectorate of Bohemia-Moravia - Moskowitz, Moses; American Jewish Committee (New York : American Jewish Committee, 1942)
Bibliotheek Camille Huysmans
Overdruk uit 'Jewish social studies', 04(1942) 1
Engels
Brochure
Keywords: joods vraagstuk; Tsjecho-Slowakije.